Evaluation of Culture Media for In Vitro Conservation of Gladiolus Cultivars - Budiarto, Kurniawan; L. Rosario, Teresita (AGRIVITA, Journal of Agricultural Science, 2020)
In vitro conservation is recognized as one promising tool in conserving plant genetic resources like gladiolus when grown in the tropics. The study was conducted at the Indonesian Ornamental Crops Research Institute (IOCRI) from February 2016 to August 2018. A complete factorial experiment was set up to establish the combination of gladiolus cultivars and media compositions treatments for in vitro conservation. The results showed that the trends of plantlet survival rate and viability in every 4 months’ observation of both cultivars were similar. The highest plantlet death rate was detected during 12 – 16 months. After 24 months of storage, the differences in plantlet survival and viability were observed. Gladiolus ‘Nafa’ had higher plantlet survivals and viability than ‘Kaifa’. In respect to nutrient and sucrose concentration, full nutrient strength preserved 5% higher plantlet survival and viability than ½ MS. While media contained sucrose 90 g/l also supported plantlet survival and viability for more than 20% and 17%, respectively than lower sucrose media.